The Sea Urchin (Echinoidea) from Panjang Island Water, Bangka Belitung Province - Siti Aisyah Lubis; Rofiza Yolanda; Arief Anthonius Purnama; Ria Karno (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
This study has been conducted from May to July 2016 in Panjang island, Bangka Tengah District,Bangka Belitung Province. The aims of this study was to evaluate the species of sea urchins by usingsurvey method at four sites. Sampling was done by using a square transect of 50 x 50 m. A total of868 individuals of sea urchin belonging to 2 species were recorded in this study, namely Diademasetosum and Echinothrix calamaris. D. setosum was the most abundant in individual number (828individuals) meanwhile E. calamaris only 40 individuals.Keywords: Diadema setosum, Echi nothrix calamaris, reef flat